2021
DOI: 10.20491/isarder.2021.1315
|View full text |Cite
|
Sign up to set email alerts
|

A Study About The Role of Cronyism Perceptions of Tourism Employees upon Their Career Plateu

Abstract: This study was conducted tries to reveal if cronyism is a problem in tourism sector just like in others, or not. For this reason, the main purpose of this study is to measure the tourism employees' cronyism perceptions and their career plateau experience arising from cronyism.Design/methodology/approach -This study was conducted with qualitative research methods and designed with exploratory research pattern. Interviews were made with 23 employees who work in different tourism enterprises. During the interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Nevertheless, some studies have yielded significant findings regarding this subject. For instance, a study conducted by Yavuz Aksakal & Ulucan (2021) discovered that employees in the tourism sector perceived a high level of nepotism, adversely impacting their affective organisational commitment, performance, and overall job satisfaction. Similarly, Pelit et al (2017) found that nepotism is widespread in Turkish tourism businesses, resulting in low levels of employee job satisfaction.…”
Section: Neptotismmentioning
confidence: 99%
“…Nevertheless, some studies have yielded significant findings regarding this subject. For instance, a study conducted by Yavuz Aksakal & Ulucan (2021) discovered that employees in the tourism sector perceived a high level of nepotism, adversely impacting their affective organisational commitment, performance, and overall job satisfaction. Similarly, Pelit et al (2017) found that nepotism is widespread in Turkish tourism businesses, resulting in low levels of employee job satisfaction.…”
Section: Neptotismmentioning
confidence: 99%